The association between stress and eating behavior among usm school of health sciences undergraduate students - Lidon, Nur Ashiken (Universiti Sains Malaysia, 2024)
University students' high stress levels due to course load may influence their eating behaviour, leading to overeating or undereating as a response to negative emotional states, impacting their health and daily life. Thus, this cross-sectional study aims to determine the association between stress and eating behaviour among USM health sciences undergraduate students. A total of 127 students were recruited using the convenience sampling method and were given a self-administered questionnaire consisting of sociodemographic items, Perceived Stress Scale (PSS-10), and Adult Eating Behaviour Questionnaire (AEBQ). There are 8 subdomain of eating behaviours which are hunger, food responsiveness, emotional overeating, enjoyment of food, satiety responsiveness, emotional undereating, food fussiness and slowness in eating. Of 127 students, 84.3% were female with majority from Dietetics program. 82.7% of the students aged 19-23 years old and 54.3% were year 3 students with the majority of 70.9% were Malay students. For household income, 60.6% of the students were from low-income families <RM4850). Regarding stress level, 85% students had a moderate level of stress with a mean of 19.51. There is a significant, weak and positive relationship between stress and hunger (p= 0.026, r= 0.197). On the other hand, there is a significant, weak and positive relationship between stress and emotional overeating (p= 0.026, r= 0.197). Others sub domains under AEBQ showed no significant relationship. Both are tested using Pearson’s Correlation test. The results imply that the students' stress levels were moderate and that their eating habits were oriented towards hunger and emotional overeating. Further research is needed to confirm recent studies and understand the association between stress and eating behaviour among undergraduate students.